Pimpinan Level Menengah yang Buruk Komunikasinya: Haruskah Karyawan Keluar? - Siti Mahmudah; Thomas Aquino Prapancha Hary; Arundati Shinta; Reny Suryani; Dewi Handayani Harahap (Jurnal Psikologi, 2020)
Objective of this literature review is to understand on how employees’ strategies to support their mental health status. This is very important since they have to engage in an organization which their boss has poor communication style. The boss in this research means the middle manager. Roots of poor communication style among middle managers are culture and improperly promotion inside organization. Although the organization has been managed improperly, interestingly, some employees still engage loyally. Unfortunately, loyalty does not reflect good mental health status. It is because loyalty is influenced strongly by external factors such as highly unemployment rate. The best strategy to adapt in that inconvenience work situation is enhancing self-quality. Hoping the boss will improve his / her communication style is more likely unrealistic.